The changing pattern of undernutrition in India: A comparative analysis across regions - Brinda Viswanathan; J. V. Meenakshi (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
This study analyses the changes in prevalence of undernutrition between the 1980s and 1990s at the national and sub-national levels in India and focuses on the rural-urban comparisons. The study exploits the demographic information available in household surveys to derive a household-specific norm as the calorie cutoff point to measure undernutrition, instead of the single per capita norm used in most other studies. The main findings of the study are: There has been an apparent increase in the prevalence of undernutrition over time in rural India, while in urban areas, the prevalence has remained unchanged, or has declined. Also, over time, average intakes in urban areas have surpassed those in rural India in most states. At the same time, there appears to be a decline in the within-state inequalities in energy intakes between 1983 and 1993/94, but an increase (especially in urban areas) between 1993/94 and 1999/2000. Income elasticities of energy demand, estimated using household-level data, are large and significant, especially among the poor. There is some evidence that, despite declining energy intakes in rural areas, there has also been some dietary diversification. However, in comparison with other developing nations, the prevalence of undernutrition is high and the level of dietary diversification is low in India. – calories ; consumption ; poverty ; India
Keywords: I12; I31; O10; R11; 330; Unterernährung; Räumliche Verteilung; Indien